From Silence to Voice: Collective Memory and Representation of Victims of the May 1998 Tragedy in Surakarta - Nur Cahya Mulianggi; Reka Maya Najwa (Konsultan Jurnal Ilmiah Indonesia, 2025)
The May 1998 riots were a historical juncture demonstrating systematic discrimination against Chinese people, which had been constructed and legitimized through the forced assimilation policy during the New Order era. The economic crisis and political instability at the time were mere sparks; the root of the problem lay in social construction, deliberately created to position ethnic Chinese as scapegoats. This research explicitly rejects the blaming narrative against the Chinese community as a source of conflict and underscores how ethnicity has been politicized to protect powerful interests. This study employed qualitative research related to literature review and critical discourse analysis. The findings show that discrimination extends beyond physical violence and looting to repression of cultural expression, inequality in legal structures, and state neglect of the human rights of minorities. Therefore, post-riot recovery must be directed not only at upholding justice but also at restoring interethnic relations and eliminating discriminatory practices in social policy and culture. This research emphasizes the urgency of national reconciliation that truly acknowledges the victims' experiences and ensures that similar tragedies do not recur.